General data protection regulation (GDPR) - Gordon, Adam; Lowrie, Daniel; Rodrick, Mike; Boose, Cherokee (Packt Publishing, 2024)
The course begins with an in-depth exploration of the General Data Protection Regulation (GDPR), laying the foundational principles that underpin data protection in the digital age. It unpacks the significance of GDPR for businesses and individuals, emphasizing the importance of compliance in today's data-driven world. By dissecting the regulation piece by piece, the course offers clear, accessible insights into its complexities. The course focuses on key areas including the principles of GDPR, special topics such as consent, data breaches, and transfers of personal data, along with a detailed examination of individual rights under GDPR. This structured approach demystifies each component, making it easier to understand how GDPR affects various aspects of data handling and privacy. The course wraps up by addressing the crucial elements of accountability and governance, preparing you to implement GDPR-compliant strategies within your organization. Through this journey, you will gain the knowledge and tools necessary to navigate the requirements of GDPR, ensuring your business or organization not only complies with the regulation but also upholds the highest standards of data protection. What you will learn Understand GDPR's core principles Navigate GDPR compliance requirements Manage data breaches and notifications Enhance data protection and privacy Handle cross-border data transfers Apply GDPR in organizational contexts Audience This course is ideal for data protection officers, compliance managers, IT professionals, and legal advisors. Basic knowledge of data protection laws is beneficial. Perfect for those looking to ensure GDPR compliance within their organizations. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Adam Gordon: Adam Gordon has 30+ years as an IT instructor in the private and public sectors. He holds more than 160 IT certifications. He has trained thousands of IT pros over the course of his career. He has over 160 professional and IT certifications. Daniel Lowrie: Daniel Lowrie's IT career began with workstation support and Y2K compliance updates for a teaching hospital in North-Central Florida. His journey led him to become an in-classroom trainer and Mentored Learning Instructor, specializing in courses covering Microsoft Windows Desktops and Servers, Active Directory, Networking, CCNA, and Linux. He then transitioned to becoming a Systems and Network administrator for a large insurance company before joining ACI Learning as an Edutainer. Certifications: CompTIA A+, Network+, Linux+, CySA+, and PenTest+; CEH; MCSA; CFR; eJPT Mike Rodrick: Mike Rodrick, the host, has more than 15 years of IT instruction experience, including 10 years as a Microsoft Certified Trainer. Mike became an ITProTV Edutainer in 2014. Certifications: GIAC Security Essentials; Azure Fundamentals; Microsoft 365 Fundamentals; Cybersec First Responder; CompTIA ITF+, A+, Network+, Security+, Project+; MCP; MCT; MCDST; MCITP; MCTS; MCSA; MCSE; MCDBA; Certified Ethical Hacker; Certified Wireless Administrator; Certified Internet Web Professional Cherokee Boose: Cherokee Boose started as a computer technician and moved to a network administrator role. Her love for learning is what pushed her towards a career in IT education. Certifications: MCSE Cloud Platform and Infrastructure; MCSA: Server 2012; MCT; MCP; MTA: Networking Fundamentals; MTA: Windows Operating System Fundamentals; Six Sigma Green Belt; CompTIA A+, A+ CE, Network+, CTT+, and Cloud+.
Online resource; title from title details screen (O'Reilly, viewed March 4, 2024)
Keywords: Computer security; Data protection; Sécurité informatique; Protection de l'information (Informatique); Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet